Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Chimpanzees use observed temporal directionality to learn novel causal relations - Claudio Tennie; Christoph J. Völter; Victoria Vonau; Daniel Hanus; Josep Call; Michael Tomasello (Primates, 2019)
We investigated whether chimpanzees use the temporal sequence of external events to determine causation. Seventeen chimpanzees ( Pan troglodytes ) witnessed a human experimenter press a button in two different conditions. When she pressed the “causal button” the delivery of juice and a sound immediately followed (cause-then-effect). In contrast, she pressed the “non-causal button” only after the delivery of juice and sound (effect-then-cause). When given the opportunity to produce the desired juice delivery themselves, the chimpanzees preferentially pressed the causal button, i.e., the one that preceded the effect. Importantly, they did so in their first test trial and even though both buttons were equally associated with juice delivery. This outcome suggests that chimpanzees, like human children, do not rely solely on their own actions to make use of novel causal relations, but they can learn causal sequences based on observation alone. We discuss these findings in relation to the literature on causal inferences as well as associative learning.

Dispersal and mating strategies in two neotropical soil-feeding termites, Embiratermes neotenicus and Silvestritermes minutus (Termitidae, Syntermitinae) - R. Fougeyrollas; K. Dolejšová; J. Křivánek; D. Sillam-Dussès; Y. Roisin; R. Hanus; V. Roy (Insectes Sociaux, 2018)

Asexual queen succession mediates an accelerated colony life cycle in the termite Silvestritermes minutus - R. Fougeyrollas; J. Křivánek; V. Roy; K. Dolejšová; S. Frechault; Y. Roisin; R. Hanus; D. Sillam‐Dussès (Molecular Ecology, 2017)
Mixed modes of reproduction, combining sexual processes with thelytokous parthenogenesis, occur in all major clades of social insects. In several species of termites, queens maximize their genetic input into nondispersing replacement queens through parthenogenesis, while maintaining genetically diverse sterile offspring and dispersing reproductives via sexual reproduction. This so‐called asexual queen succession ( AQS ) has multiple independent origins and its presumed advantages are diverse as well, ranging from multiplication of colony reproductive potential to extension of its lifespan beyond that of the foundress. However, how AQS shapes colony life cycles under natural conditions remains poorly known. The neotropical termite Silvestritermes minutus inhabits small but conspicuous nests, offering a unique opportunity to investigate the impact of AQS on life history. We report on its breeding system, life cycle and sex allocation using social structure census in 137 nests and genotyping of 12 colonies at 12 microsatellite loci. We show that colonies are established by an outbred pair of primary reproductives. In less than 2 years, the foundress is replaced by multiple neotenic queens, arising mostly through automixis with central fusion. Sterile castes, male and most (93%) female dispersers are produced sexually. Colony reproduction is usually restricted to a single dispersal of alates with unbiased sex ratio, taking place after 3 years. We conclude that S. minutus benefits from AQS to maximize colony growth rate and alate production within a very short life cycle rather than to extend colony lifespan. This highlights the versatile role of AQS in different cases of its polyphyletic origin.

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

The Phenomenon of Ischemic Postconditioning of the Heart - L. N. Maslov; A. G. Mrochek; L. Hanus; J.-M. Pei; Y. Zhang; H. Wang; N. V. Naryzhnaya (Neuroscience and Behavioral Physiology, 2014)

Safety of atmospheric storage tanks during accidental explosions - E. Noret; G. Prod'homme; T. Yalamas; M. Reimeringer; J.-L. Hanus; D.-H. Duong (European Journal of Environmental and Civil Engineering, 2012)

Response of a tank under blast loading -- part I: experimental characterisation of blast loading arising from a gas explosion - D.H. Duong; J.L. Hanus; L. Bouazaoui; O. Pennetier; J. Moriceau; G. Prod’homme; M. Reimeringer (European Journal of Environmental and Civil Engineering, 2012)

Sexual communication in the termite Prorhinotermes simplex (Isoptera, Rhinotermitidae) mediated by a pheromone from female tergal glands - R. Hanus; A. Luxová; J. Šobotník; B. Kalinová; P. Jiroš; J. Křeček; T. Bourguignon; C. Bordereau (Insectes Sociaux, 2009)

The ontogeny of soldiers in Prorhinotermes simplex (Isoptera, Rhinotermitidae) - R. Hanus; J. Šobotník; I. Valterová; J. Lukáš (Insectes Sociaux, 2006)

Egg care by termite soldiers - R. Hanus; J. Šobotník; L. Cizek (Insectes Sociaux, 2005)

Hydrogen production and uptake by pea nodules as affected by strains of Rhizobium leguminosarum - Tomas Ruiz-Argeso; Joe Hanus; Harold J. Evans (Archives of Microbiology, 1978)

The effect of agar on the inhibitory activities of fatty amines - F. J. Hanus; E. O. Bennett (Antonie van Leeuwenhoek, 1964)